Analisis Perhitungan Biaya Produksi Menggunakan Metode Full Costing Sebagai Dasar Penentuan Harga Jual Produk - Ammi Nadira, Daffa Aqila; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This research aims to analyze the calculation of production costs using the full costing method as a basis for determining product selling prices at the "Kaya Rasa" Fish Crackers Factory in Tunggal Warga Village, Banjar Agung District, Tulang Bawang Regency. The research method used is a descriptive method with a qualitative approach. The object of this research is the "Rich Taste" Fish Crackers Factory. The type of data in this research is qualitative data and the data source in this research is primary data. Data collection techniques in this research are observation, interviews and documentation. This research uses the full costing method so that production cost information becomes more accurate. The results of the research show that calculating production costs using the full costing method produces higher and more detailed prices than the method applied by the "Kaya Rasa" Fish Crackers Factory, so that the full costing method can be used as a basis for determining competitive selling prices and generating optimal profits.